واقعہ اصحاب کہف کامفسرین کی آراء کی روشنی میں تجزیاتی مطالعہ: An Analytical Study of the Incident of Ashab al-Kahf in the Light of the Opinions of the commentators - Dr.Hafiz.M.Mudassar Shafique; Saira Tariq; Muhammad Shoaib (Al Manhal Research Journal, 2024)
Qur'an is the book of knowledge and wisdom which not only gave life to the sciences but also helped in the creation of numerous modern sciences. Many scholars with taste in different periods of Islamic history have researched the interpretation of the Qur'an in their own way. The first exegete to explain the teachings of the Qur'an was the Holy Prophet himself, who set an exegetical model by his own practice. And then some of the Companions took ownership of it. In this way, as soon as Islam spread to different countries, scholars adapted the interpretation of the Qur'an according to their principles. All the commentators interpreted the Qur'an thanks to their knowledge.Therefore, its interpretation has a special importance in the subcontinent, therefore many such events are mentioned in the Qur'an whose historical status is of great importance.One of these events is Ashab al-Kahf which has its own identity in terms of history and research. In this article, an analytical study has been done in view of the opinions of various commentators on the incident of Ashab al-Kahf.